Management and Economy in Hartals: The Case of Bangladesh - Rahman, Khondaker (Journal of Comparative International Management)

(untitled) (Management Futures, 2014)
Based on the secondary sources and interviews, this paper gives an account of hartal and similar political activities, examining the economic and social impacts of such activities on the economy of Bangladesh and the management of the companies in that country. As hartal and associated activities are not well defined in literature, this study begins by giving a brief definition and description of those activities. The findings of the study suggest that these activities are organized to ensure freedom of assembly, expression of opinion, and political rights by raising protests against certain government actions and policies. However, in reality, and especially during the last two decades, much of these activities have been used as a vindictive movement against the political party in the helm of the regime. The study also found that hartal and similar activities have resulted in colossal economic losses of work, working hours, business management, industrial output, business capital, property, and human life, as well as visible and non-visible social losses, such as human distress, loss of human life, uncertainly, chaos, hatred, disunity among people, and erosion of the national image. Finally, this study found that people engaged in economic activities dislike such political activities, considering them as unnecessary evils, and want political parties to work on creating alternative, peaceful action programs. The paper finally gives some suggestions to solve the problem of hartal and relieve the miseries that come along with it.